MENGUKUR KINERJA KEUANGAN PT BANK SYARIAH TBK DI BURSA EFEK INDONESIA PADA RENTANG WAKTU 2021-2023 DENGAN ANALISIS RASIO SOLVABILITAS - Vena Tri Pramita; Salsabila Nuri. W, Jalaluddin I.R, Renny Oktafia (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
Sharia banking is a banking institution that uses Islamic principles in providing financial services to the public. Financial performance is an analysis used to determine whether a banking institution has implemented the provisions stipulated in a good and correct financial management system. The aim of this study is to determine whether the financial ratios used can be evaluated from bank financial reports over the last three years, namely 2021-2023, to determine the results of the bank's financial performance. In this research, the method used is a quantitative research method. And to obtain the data needed for this research, the approach used was literature study and documentation. The data in the research were analyzed descriptively quantitatively using a case study approach. This approach focuses on in-depth study of a particular object to understand the relevant case. The aim is to understand a detailed description of the characteristics, background and nature of the case, which can then be linked to general concepts. The results of research conducted by PT Bank Syariah Tbk show healthy financial performance in the 2021-2023 period on the Indonesia Stock Exchange